2020
DOI: 10.1038/s41598-020-69530-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of azelaic and pyruvic acid peels in the treatment of female adult acne: a randomized controlled trial

Abstract: chemical peels are widely used as therapeutic agents in dermatology and cosmetology. this study aims to explore the differences in the effectiveness of azelaic and pyruvic acid peels in the treatment of acne vulgaris. Eligibility criteria for participants were: female gender, 18-25 years of age, no dermatological treatment within the last 12 months and mild to moderate papulopustular acne. We treated 120 young women (with a mean age of 22 years old) with six peeling sessions at 2-week intervals. In the paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 27 publications
0
20
0
8
Order By: Relevance
“…Previous research has shown the effectiveness of cosmeceutical treatment for improving skin parameters and reducing the scars of people with acne vulgaris, using acid peels, radiofrequency, and fractional microneedle radiofrequency, microdermabrasion, sonophoresis, and intense pulsed light (IPL) [ 25 , 49 , 50 ]. Compared to other topical cosmeceutical treatments, such as cosmetic acids [ 9 , 50 ], the hydrogen purification treatment is not associated with the risk of irritation, reddening of the skin, or side effects as burning and itching of the epidermis surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown the effectiveness of cosmeceutical treatment for improving skin parameters and reducing the scars of people with acne vulgaris, using acid peels, radiofrequency, and fractional microneedle radiofrequency, microdermabrasion, sonophoresis, and intense pulsed light (IPL) [ 25 , 49 , 50 ]. Compared to other topical cosmeceutical treatments, such as cosmetic acids [ 9 , 50 ], the hydrogen purification treatment is not associated with the risk of irritation, reddening of the skin, or side effects as burning and itching of the epidermis surface.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown the effectiveness of cosmeceutical treatment for improving skin parameters and reducing the scars of people with acne vulgaris, using acid peels, radiofrequency, and fractional microneedle radiofrequency, microdermabrasion, sonophoresis, and intense pulsed light (IPL) [ 25 , 49 , 50 ]. Compared to other topical cosmeceutical treatments, such as cosmetic acids [ 9 , 50 ], the hydrogen purification treatment is not associated with the risk of irritation, reddening of the skin, or side effects as burning and itching of the epidermis surface. People with sensitive skin, prone to irritation and with certain undesirable symptoms related to the type of skin (e.g., dryness, tightness, coarseness, washout of makeup, quick production of sebum, feeling differences in oiliness, frequencies of acne lesions, and oiliness) [ 51 ], should pay special attention to treatments with the use of cosmetic acids or other topical therapies [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of acne vulgaris was assessed using the Hellgren–Vincent Scale (HVS). In the HVS, the number of skin eruptions in people suffering from acne are classified using a five-point scale, as follows: (1) erythema, blackheads, and 1–5 pustules or papules; (2) erythema, blackheads, and 6–10 pustules or papules; (3) erythema, blackheads, and 11–20 pustules or papules; (4) erythema, blackheads, and 21–30 pustules or papules; (5) erythema, blackheads, and over 30 pustules or papules [ 93 ]. In the AV group, all participants presented with mild acne, including 96 (64%) women with first-degree acne severity and 54 (36%) females with second-degree acne severity based on the HVS.…”
Section: Methodsmentioning
confidence: 99%
“…In females, acne is more persistent and commonly located on the face, while males experience more severe forms with eruptions located mostly on the chest and back. Acne occurs also in the adult population, not only in teenagers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%